A Perspective on Higher Education Through the Lens of a Student Activist (LEARNing Landscapes, 2010)
Both historically and present day, students and youth have been at the forefront of social justice movements. Environmental justice, defence of undocumented students, whistleblower protection, international solidarity and labour rights are among a myriad of issues which have emerged to expand the range and scope of equitable education politics within student movements. This commentary provides a perspective on higher education through the lens of one student activist. This reflection shares some thoughts on the implications of high tuition fees for marginalized communities and emphasizes the importance of youth activism in advancing the struggle for accessible postsecondary education and socioeconomic justice domestically and abroad.
Keywords: equitable education politics; education; higher education; activism; social justice; student; youth; accessibility; international solidarity